2020
DOI: 10.1002/ajcp.12454
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Criminal Record Stigma on Quality of Life: A Test of Theoretical Pathways

Abstract: Across multiple stigmatized groups, research suggests that stigma may negatively impact individual wellbeing. This impact often occurs through a sequential pathway that includes perceiving societal stigma, a diminished and stereotyped self‐concept (i.e., internalized stigma), experiences of discrimination and rejection, and attempts to cope with stigma (e.g., secrecy or withdrawal). While prior research supports individual links within this pathway, no study has evaluated a model representing the relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 41 publications
(148 reference statements)
0
22
0
2
Order By: Relevance
“…West et al (2015) found that higher internalized stigma was associated with greater racial self-concept (i.e., more positive attitudes toward one's racial/ethnic group), though results were not stratified by racial/ethnic group. McWilliams and Hunter (2020) found no association between internalized stigma and offense type, participant age, nor time incarcerated, though female participants were found to report significantly lower rates of internalized stigma compared with male participants (b = -.17, p , .05).…”
Section: Correlates Of Internalized Sigmamentioning
confidence: 72%
See 3 more Smart Citations
“…West et al (2015) found that higher internalized stigma was associated with greater racial self-concept (i.e., more positive attitudes toward one's racial/ethnic group), though results were not stratified by racial/ethnic group. McWilliams and Hunter (2020) found no association between internalized stigma and offense type, participant age, nor time incarcerated, though female participants were found to report significantly lower rates of internalized stigma compared with male participants (b = -.17, p , .05).…”
Section: Correlates Of Internalized Sigmamentioning
confidence: 72%
“…In the present study, the negative effects of incarceration-related stigma on health (Redmond et al, 2020), employment (Moore et al, 2013), and broader indicators of well-being (McWilliams & Hunter, 2020; suggest that there is much work to be done to reduce the collateral consequences that formerly incarcerated persons experience upon reentry. Individuals experiencing overt discrimination and anticipatory distress related to seeking supportive health care services and employment need individual, community, and public policy strategies to reduce the damaging impact of criminal record stigma.…”
Section: Practical and Policy Implicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…Zielinski et al also report on successful features of community‐university partnerships, calling particular attention to the importance of partnership participants making a unique contribution to the collaborative work. Finally, the first half of the special issue closes out with work from McWilliams and Hunter (2021) focusing on the needs of individuals with prior criminal convictions. McWilliams and Hunter explore how stigma associated with a prior felony or misdemeanor conviction negatively impacts quality of life among individuals with criminal records.…”
mentioning
confidence: 99%